Overview of SARS-CoV-2 infection in adults living with HIV. Issue 5 (May 2021) - Ambrosioni, Juan; Blanco, José Luis; Reyes-Urueña, Juliana M; Davies, Mary-Ann; Sued, Omar; Marcos, Maria Angeles; Martínez, Esteban; Bertagnolio, Silvia; Alcamí, Jose; Miro, Jose M; ,; Ambrosioni, Juan; et al.
Summary: Around 2·5 million deaths and more than 110 million COVID-19 cases have been reported globally. Although it initially appeared that HIV infection was not a risk factor for COVID-19 or more severe disease, more recent large studies suggest that people living with HIV (particularly with low CD4 cell counts or untreated HIV infection) might have a more severe clinical course than those who are HIV-negative. Moreover, the COVID-19 pandemic has disrupted HIV prevention and treatment services worldwide, creating huge challenges to the continuity of essential activities. We have reviewed the most relevant features of COVID-19 in people living with HIV and highlighted topics where further research is required.